(untitled) (Journal of Partial Differential Equations, 2000)
In this paper, we consider the existence and uniqueness of the radial ground state to the following p-Laplacian equation involving super-critical or critical exponents: Δ_pu + u^q - |Du|^σ = 0, x ∈ R^n, 2 ≤ p < n, q ≥ [n(p - 1) + p]/(n - p), σ > 0. Applying the shooting argument, the Schauder's fixed point theorem and some delicate estimates of auxiliary functions, we study the influence of the parameters n, p, q, σ on the existence and uniqueness of the radial ground state to the above p-Laplacian equation.